Efficacy and safety of lumacaftor and ivacaftor in patients aged 6–11 years with cystic fibrosis homozygous for F508del-CFTR: a randomised, placebo-controlled phase 3 trial. Issue 7 (July 2017) - Ratjen, Felix; Hug, Christopher; Marigowda, Gautham; Tian, Simon; Huang, Xiaohong; Stanojevic, Sanja; Milla, Carlos E; Robinson, Paul D; Waltz, David; Davies, Jane C; ,
Summary: Background: Lumacaftor and ivacaftor combination treatment showed efficacy in patients aged 12 years or older with cystic fibrosis homozygous for F508del-cystic fibrosis transmembrane conductance regulator (CFTR) in placebo-controlled studies and patients aged 6–11 years with cystic fibrosis homozygous for F508del-CFTR in an open-label study. We report efficacy and safety of lumacaftor and ivacaftor in patients with cystic fibrosis aged 6–11 years homozygous for F508del-CFTR . Methods: In this phase 3, randomised, double-blind, placebo-controlled, multicentre study, patients were enrolled at 54 hospitals and medical centres in nine countries (the USA, Australia, Belgium, Canada, Denmark, France, Germany, Sweden, and the UK). Eligible patients weighed at least 15 kg, with a confirmed diagnosis of cystic fibrosis, percent predicted forced expiratory volume in 1 s (FEV1 ) of 70 or more, and lung clearance index2·5 (LCI2·5 ) of 7·5 or more at screening (values less than these thresholds were permitted at day 1). All patients were tested for CFTR genotype at screening; eligible patients had to have the F508del-CFTR mutation on both alleles. Exclusion criteria included any comorbidity or laboratory abnormality that might confound the study results or pose additional risk to the patient. Patients were stratified by weight (<25 kg vs ≥25 kg) and ppFEV1 severity (<90 vs ≥90) determined at the screening visit, and randomly assigned 1:1 to treatment using an interactive web response system to receive 200 mg lumacaftor and 250 mg ivacaftor every 12 hours or placebo for 24 weeks. Patients, all site personnel including the investigator and the site monitor, and the study team were blinded, with the exception of site personnel needing this information in the event of medical emergency or pregnancy and patient safety and regulatory affairs personnel to meet serious adverse event reporting requirements. The primary endpoint was the mean absolute change in LCI2·5 from all study visits up to and including week 24. All randomly assigned patients who were exposed to any amount of study drug, with treatment assignment as assigned were included in primary and other efficacy analyses. All patients who were exposed to any amount of study drug, with treatment assignment as treated, were included in the safety analysis. This study was registered withClinicalTrials.gov, numberNCT02514473 . Findings: Between July 23, 2015, and Sept 20, 2016, a total of 206 patients were enrolled and randomly assigned to receive lumacaftor and ivacaftor (n=104) or placebo (n=102). Two randomly assigned patients were never dosed with study drug (one in the placebo arm due to ineligibility arising from a streptococcal throat infection and one in the lumacaftor and ivacaftor arm due to withdrawal based on refusal to provide blood tests) and were not included in the analyses. 103 patients received at least one dose of lumacaftor and ivacaftor and 101 patients received at least one dose of placebo. For the primary endpoint, the average absolute change in LCI2·5 from baseline over all study visits up to and including the week 24 visit, least squares mean difference was −1·09 units (95% CI −1·43 to −0·75, p<0·0001) for lumacaftor and ivacaftor versus placebo. For the key secondary endpoint of sweat chloride concentration, the least squares mean difference versus placebo was −20·8 mmol/L (95% CI −23·4 to −18·2, average absolute change at day 15/week 4; p<0·0001). The least squares mean difference compared with placebo in absolute change in ppFEV1 from all study visits until week 24 was 2·4 (95% CI 0·4–4·4, p=0·0182). 196 (96%) of 204 patients reported adverse events, most of which were mild (87 [43%]) or moderate (98 [48%]). Treatment was discontinued due to adverse events in three (3%) of 103 patients in the lumacaftor and ivacaftor group and two (2%) of 101 patients in the placebo group. Serious adverse events were reported in 13 (13%) of 103 patients in the lumacaftor and ivacaftor group and 11 (11%) of 101 patients in the placebo group. Interpretation: Treatment with lumacaftor and ivacaftor was associated with statistically significant improvements in lung function, as measured by LCI2·5 and ppFEV1, versus placebo in patients aged 6–11 years with cystic fibrosis homozygous for F508del-CFTR . The overall safety profile was consistent with previous phase 3 studies of lumacaftor and ivacaftor. Funding: Vertex Pharmaceuticals.